PREVALENCE OF GLAUCOMA IN PSEUDO EXFOLIATION SYNDROMEPATIENTS AT A TERTIARY CARE CENTER IN JAMMU & KASHMIR (INDIA) (Applied Biological Research, 2024)
Pseudo exfoliation syndrome (PEX), an age-related disorder, is a systemic extracellular matrix condition that largely manifests as distinctive ocular characteristics. Glaucoma, a clinical consequence of PEX, in exfoliation syndrome is more severe than primary open-angle glaucoma. Increased intraocular pressures and its diurnal variation are typically higher at diagnosis time, and visual field abnormalities are typically severe in exfoliation glaucoma. The present study was aimed to assess the prevalence of glaucoma in PEX patients who underwent a comprehensive ophthalmic evaluation in a tertiary care centre. An institution-based cross sectional study was conducted in ASCOMS & Hospital, Jammu (India) from June to November, 2023 involving 115 clinically diagnosed PEX patients (190 eyes) of age >50 years. Demographic information related to their age, sex, religion, residence and alcohol addiction was collected and glaucoma in PEX patients, if present, ascertained. The comprehensive ophthalmological evaluation undertaken included recording diurnal variation of tension, gonioscopy and visual field assessment. The study revealed the prevalence of glaucoma as 32.85% among PEX patients with mean intraocular pressure as 17.3 ± 3.7 mmHg. A significant association between glaucoma in PEX patients with age, sex and residence was observed. PEX patients of age-category 61-70 (86.4%), male (40.3%), Hindu (41.7%), urban people (45.3%) and alcohol addicted (42.2%) suffered more from glaucoma. Among the PEX patients having bilateral involvement (65.2%), glaucoma prevailed in 34.7% cases, while glaucoma was recorded in 45.0% of the rest PEX patients showing unilateral involvement. PEX is a major significant risk factor in glaucoma development. The patients suffering from PEX should get frequently examined so as to prevent the risk of glaucoma development.
Keywords: Glaucoma; intraocular pressure; ocular problem; pseudo exfoliation syndrome; vision